Operationalizing a 3-year standalone, accelerated medical school curriculum to nurture physicians to become primary care and health system leaders - Maria Lyn Quintos-Alagheband; Orla O’Donoghue; Gladys M. Ayala; Steven Carsons; Nobuyuki Miyawaki; Arsenia Asuncion; Francis Faustino; Patricia Janicke; Jeffrey Berger; Dana Ribeiro Miller; Clothilde Castiglia; Isabella Harnick; et al. (Medical Education Online)
The United States faces a shortage of primary care physicians. To address this, there have been pioneering efforts to develop accelerated pathways with a primary care focused curriculum for undergraduate medical education. The New York University Grossman Long Island School of Medicine (NYU GLISOM) was conceptualized as the first standalone, accelerated, tuition-free program in the US in over 100 years, with mission-centered curriculum on primary care and health system leadership. The aim of this article is to map the process for the development of a three-year integrated curriculum, describe the pedagogical approach that guided the design of the longitudinal courses, share the student and faculty’s perspective about the curriculum, and describe the early outcomes of the first two graduate classes. A major key driver for curricular design is integrating longitudinal courses of Clinical Ambulatory Practice Experience (CAPE), Health Systems Science (HSS), and Learning Community - Social Sciences, Humanities, Ethics and Professionalism (LC-SHEP) over three years and active learning through Problem Based Learning (PBL). We have successfully operationalized an accelerated, standalone, integrated medical school curriculum mission-centered on primary care and health system leadership. Our outcomes reveal a higher percentage (76% N =45) of NYU GLISOM students entering primary care compared to national benchmarks. The integration of the longitudinal courses of HSS, LC-SHEP, and CAPE is a key pillar to reinforce the tenants of primary care and health system leadership. Focused interview of graduates from the pioneer cohort consistently stated that the longitudinal courses prepared them well for residency in primary care and as a health systems’ change agent. Despite the challenges of an accelerated program, NYU GLISOM successfully integrated the longitudinal courses with optimal performance and achievement of educational program objectives. Our experience can serve as a model for innovation and design of an accelerated three-year primary care curriculum.